2010
DOI: 10.1074/jbc.m109.093666
|View full text |Cite
|
Sign up to set email alerts
|

Recessive COL6A2 C-globular Missense Mutations in Ullrich Congenital Muscular Dystrophy

Abstract: Ullrich congenital muscular dystrophy (UCMD) is a disabling and life-threatening disorder resulting from either recessive or dominant mutations in genes encoding collagen VI. Although the majority of the recessive UCMD cases have frameshift or nonsense mutations in COL6A1, COL6A2, or COL6A3, recessive structural mutations in the COL6A2 C-globular region are emerging also. However, the underlying molecular mechanisms have remained elusive. Here we identified a homozygous COL6A2 E624K mutation (C1 subdomain) and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
14
0

Year Published

2010
2010
2019
2019

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 24 publications
(17 citation statements)
references
References 39 publications
3
14
0
Order By: Relevance
“…Secreted tetramers are not able to form microfibrils and pathology results because there are no collagen VI supramolecular structures in the extracellular matrix. Monomer, dimer, and tetramer formation are also not affected by the ␣2(VI) C1 domain substitution, p.E624K (38). In contrast to UCMD21, secreted tetramers with the ␣2(VI) p.E624K mutation form microfibrils in the extracellular matrix, although when viewed by electron microscopy they appear disorganized.…”
Section: Discussionmentioning
confidence: 92%
See 1 more Smart Citation
“…Secreted tetramers are not able to form microfibrils and pathology results because there are no collagen VI supramolecular structures in the extracellular matrix. Monomer, dimer, and tetramer formation are also not affected by the ␣2(VI) C1 domain substitution, p.E624K (38). In contrast to UCMD21, secreted tetramers with the ␣2(VI) p.E624K mutation form microfibrils in the extracellular matrix, although when viewed by electron microscopy they appear disorganized.…”
Section: Discussionmentioning
confidence: 92%
“…To date, the mutations in this class are all in the ␣2(VI) C2 domain and include p.L873P, p.R876S, p.N897del, and p.P932L (17,18,38). ␣2(VI) chains expressing these mutations are not able to assemble into triple helical structures.…”
Section: Discussionmentioning
confidence: 99%
“…For example, a homozygous ␣2(VI) p.R876S mutation destabilizes the mutant chain and the small amount of secreted collagen VI contains the ␣2(VI) C2a chain (31). We reported a patient with recessive ␣2(VI) C2 domain mutations, p.L873P and p.N897del, and showed that the mutant chains were unstable and only small amounts of collagen VI were secreted (3).…”
Section: Discussionmentioning
confidence: 92%
“…Such mutations presumably affect crucial functions of the collagen VI protein and its interactions. 16,90 …”
Section: Properties Of Collagen VImentioning
confidence: 99%
“…32,90 In addition, mutation analysis of the collagen VI genes has led to identification of a growing number of polymorphic variants of unknown significance. These variants require careful genetic and biochemical analysis to prove or disprove their pathogenetic roles.…”
Section: Properties Of Collagen VImentioning
confidence: 99%